Impact of wind power in isolated power systems - Etxegarai, A.; Eguia, P.; Torres, E.; Fernandez, E. (2012 16th IEEE Mediterranean Electrotechnical Conference, 2012)
Weak power grids with DG penetration show poor power quality, protection issues and frequency deviations under severe disturbances, especially in isolated networks. This paper explores the impact of wind power in weak isolated power systems. A small size island power system has been modeled and the impact of wind power on system stability has been studied. Two main aspects have been covered: the impact on frequency stability and on transient stability, as well as fault-ride through capability of the wind turbines.